PENGARUH INSTRUKSI GUBERNUR NOMOR 451 TAHUN 2022 DAN MANAJEMEN PENGELOLAAN KEGIATAN TERHADAP PELAKSANAAN WIRID REMAJA DI SMK NEGERI SE KOTA PAYAKUMBUH - Dori Rusyunizal; M. Arif (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2026)
The implementation of youth devotional practices—as mandated by West Sumatra Governor’s Instruction No. 451 of 2022—at public vocational high schools throughout Payakumbuh City has not been optimal due to insufficient policy implementation and activity management. This study aims to analyze the influence of Governor’s Instruction No. 451 of 2022 and activity management on the implementation of youth devotional practices, both partially and simultaneously. The study employed a quantitative approach with an associative research design. The sample consisted of 184 teachers selected using saturation sampling. Data were collected via a questionnaire that had passed validity and reliability tests, then analyzed using multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results indicate that Governor’s Instruction No. 451 of 2022 has a positive and significant effect on the implementation of youth wirid (t = 2.317; β = 0.529; p = 0.036), while activity management exerts a stronger influence (t = 12.885; β = 0.909; p < 0.001). Simultaneously, both variables had a significant effect (F = 267.647; p < 0.001) with an Adjusted R² value of 0.747. It is concluded that the effectiveness of policy implementation and activity management plays a crucial role in enhancing the implementation of youth wirid; therefore, these aspects need to be strengthened as the foundation for developing religious character-building programs in schools.